Development Of Basic Locomotor Movement Games Based On Local Wisdom For Learning Pjok Class 1 Elementary Schools - Bangkit Seandi Taroreh; M. Haris Satria (STKIP Muhammadiyah Kuningan, 2023)
The aims of this study were 1) to produce basic locomotor motion games based on local wisdom for Class 1 Elementary School PJOK learning, 2) to find out the effectiveness of their use in learning. This study used research and development (R and D) methods with the ADDIE approach. The research population was 1st grade elementary school students in Palembang City. The sampling technique used a purposive sample totaling 42 students with criteria including 1) being a tri dharma partner school of higher education with a Universitas Bina Darma in MBKM and PPL activities, 2) grade 1 elementary school students, 3) using the 2013 curriculum. The research instrument was a questionnaire. Data analysis techniques using quantitative analysis. The results of the research included: 1) learning media products in the form of basic locomotor games based on local wisdom for PJOK first grade elementary school learning, 2) the resulting learning media products showed the effectiveness of